الاتساق المعجمي في ضوء لسانيات النص - مناني، سهام, بادي، مريم (University of El-oued, 2022)
تناولنا من خلال دراستنا في الموضوع المعنون: " الاتساق المعجمي في جزء قد سمع دراسة في ضوء لسانيات النص" قُسم إلى مدخل وفصلين, حظي المدخل بمجموعة من المفاهيم والمصطلحات التي تخدم الموضوع, والفصل الأول تناولنا فيه "أنواع التكرار في جزء قد سمع", كان ممزوج بين النظري والتطبيقي فعرفّنا فيه التكرار مع بيان أغراضه وأهميته وبيّنا كيف تنوعت عناصر التكرار في الجزء المخصّص, وقد تعددت أنواعه بين : التكرار التام والجزئي والترادف وشبه الترادف والتكرار التوازي مع تبيين كيف ساهمت هاته العناصر في الاتساق والتماسك آيات النص القرآني, أما الفصل الثاني قد خُصّص لـ: "أنواع التضام في جزء ق سمع" وقد عرفّنا فيه التضام وأهميته مع ذكر بعض من أغراضه, مع دراسة عناصره في الجزء المدروس, وقد تنوعت عناصره بين: الارتباط بموضوع معين والتضاد وعلاقة الجزء بالجزء وعلاقة الجزء بالكل. ففي النص القرآني ـ جزء قد سمع ـ عناصر الاتساق المعجمي متوفرة ومتنوعة فهذا Through our study, we dealt with the topic entitled: “Lexical consistency in a part that has been heard, a study in the light of the linguistics of the text.” It was divided into an introduction and two chapters. Mixed between theoretical and practical, we defined repetition in it with a statement of its purposes and importance, and we explained how the elements of repetition varied in the allocated part, and its types varied between: complete and partial repetition, tandem, semi-tandem and parallel repetition with an explanation of how these elements contributed to the consistency and coherence of the verses of the Qur’anic text. As for the second chapter, it is devoted to: “Types of solidarity in the part of the sama.” In it, we defined the conjunction and its importance with mentioning some of its purposes, with a study of its elements in the studied part, and its elements varied between: the connection with a specific subject, the contradiction, the relationship of the part to the part, and the relationship of the part to the whole. In the Qur’anic text - a part has heard - the elements of lexical consistency are available and varied, and this is what contributed to the casting and consistency of the elements and parts of its verses.
Keywords: لسانيات النص, الاتساق ,اليات الاتساق, الاتساق المعجمي, التكرار, التضام , التماسك, جزء قد سمع.; Linguistics of the text, consistency, mechanisms of consistency, lexical consistency, repetition, coherence, cohesion, a part has been heard.